Five-year administration of tocilizumab to a patient with rheumatoid arthritis complicated by severe chronic heart failure - Akitake SUZUKI; Toshitake TAMAMURA; Takahiro OKAI (Japanese Journal of Clinical Immunology, 2014)
[summary] We herein described the long-term administration of tocilizumab (TCZ) to a patient with rheumatoid arthritis (RA) complicated by three vessel coronary artery disease and severe heart failure (HF). A 41-year-old male was admitted to our hospital with exacerbated RA and congestive HF. Cardiac ultrasonography revealed diffuse hypokinesis with a left ventricular ejection fraction (LVEF) of 16.8% and New York Heart Association (NYHA) class III/IV HF. Swelling and tenderness were noted in most of his joints. Methotrexate (MTX) was initiated during his hospitalization and TCZ was introduced 6 months later. Our patient has been treated with MTX and TCZ for five years without any adverse events, and RA and HF have remained stable. Although it may be anecdotal, we suggest that TCZ may be used as a treatment option in patients with RA complicated by severe HF.